2020
DOI: 10.1016/j.margeo.2020.106210
|View full text |Cite
|
Sign up to set email alerts
|

Impact of river discharge on hydrodynamics and sedimentary processes at Yellow River Delta

Abstract: Highlights(1) Tide amplitude decreases in the lowermost channel and tidal flats of the Yellow River Delta as river discharge increases.(2) The river discharge changes can reshape the shear front zone dynamics near the active Yellow River delta.(3) The barrier effect of the tidal shear front zone combined with strong longshore tidal currents significantly restrict the sediment dispersal and river mouth deposits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
46
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(52 citation statements)
references
References 48 publications
6
46
0
Order By: Relevance
“…We further tested the significance of the average annual river discharge and sediment load due to the dam regulations in the two deltas (Figure 4a-d). The results showed that As for the Yellow River Delta, the river discharge and sediment load decreased gradually from 1950 to 2017 [41,66,67]. Corresponding to the construction of the four major dams (i.e., the Sanmenxia, Liujiaxia, Longyangxia, and Xiaolangdi Dams) [5], we divided the study period into five phases: phase i (1950-1960), phase ii (1961-1968), phase iii (1969)(1970)(1971)(1972)(1973)(1974)(1975)(1976)(1977)(1978)(1979)(1980)(1981)(1982)(1983)(1984)(1985), phase iv (1986-1999) and phase v (2000-2017) (we use lowercase letters to make a distinction from the different phases of the Volta River Delta, Figure 3b).…”
Section: Hydrological Alterationmentioning
confidence: 99%
“…We further tested the significance of the average annual river discharge and sediment load due to the dam regulations in the two deltas (Figure 4a-d). The results showed that As for the Yellow River Delta, the river discharge and sediment load decreased gradually from 1950 to 2017 [41,66,67]. Corresponding to the construction of the four major dams (i.e., the Sanmenxia, Liujiaxia, Longyangxia, and Xiaolangdi Dams) [5], we divided the study period into five phases: phase i (1950-1960), phase ii (1961-1968), phase iii (1969)(1970)(1971)(1972)(1973)(1974)(1975)(1976)(1977)(1978)(1979)(1980)(1981)(1982)(1983)(1984)(1985), phase iv (1986-1999) and phase v (2000-2017) (we use lowercase letters to make a distinction from the different phases of the Volta River Delta, Figure 3b).…”
Section: Hydrological Alterationmentioning
confidence: 99%
“…According to the official Yellow River Sediment Bulletin (http://www.mwr.gov.cn/sj/, accessed on 13 May 2021), six major water and sediment regulation projects were carried out between 2002 and 2010. However, both water discharge and sediment transport began to decrease after 2002 [48], in which sediment transport was small in the years (2002,2003,2004,2005,2007, and 2010) with large water volume. Artificial hydraulic engineering increases the water discharge, but the total amount of sediment load does not increase significantly, which mainly resulted in the corresponding decrease of the shoreline length in the estuary area.…”
Section: Area Change Water Discharge and Sediment Loadmentioning
confidence: 99%
“…Interactions between land, river, and ocean and the variability of water hydrodynamic conditions play an important role in the transfer, exchange, and dispersion of sediments transported by rivers. These interactions impact estuarine deposits, coastal deposits, erosion, and accumulation areas (Ji, Pan, and Chen, 2020). In this way, the upstream water flows are significant modulators of the environmental characteristics of estuaries due to the contribution and transport of particulate and dissolved compounds (Garel and D'alimonte, 2017;Haslet, 2009;Montagna, Palmer, and Pollack, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…These interactions impact estuarine deposits, coastal deposits, erosion, and accumulation areas (Ji, Pan, and Chen, 2020). In this way, the upstream water flows are significant modulators of the environmental characteristics of estuaries due to the contribution and transport of particulate and dissolved compounds (Garel and D'alimonte, 2017;Haslet, 2009;Montagna, Palmer, and Pollack, 2013).…”
Section: Introductionmentioning
confidence: 99%